MiR-92b-3p inhibits proliferation and migration of C2C12 cells. Issue 21 (1st November 2020) - Ye, Zijian; Shi, Jia; Ning, Zuocheng; Hou, Lianjie; Hu, Ching Yuan; Wang, Chong
ABSTRACT: Skeletal muscle, a critical component of the mammalian body, is essential for normal body movement. miRNAs are well documented in gene post-transcription regulation in many biological processes, including muscle development and maintenance. miR-92b-3p, which is often associated with tumorigenesis, has never been explored in myoblast development. Here, we used murine-derived C2C12 myoblasts to explore the potential functions of miR-92b-3p in skeletal muscle development. Our results demonstrated that miR-92b-3p mimics inhibited C2C12 cell proliferation and migration, whereas miR-92b-3p inhibitor promoted C2C12 cell proliferation and migration. C2C12 cell differentiation was not affected by miR-92b-3p mimics, according to immunofluorescence and qPCR results. Serum- and glucocorticoid-induced kinase 3 (SGK3) was predicted and validated as a target of miR-92b-3p. Overexpression of SGK3 promoted C2C12 cell proliferation. SGK3 and miR-92b-3p formed a regulatory pathway to modulate C2C12 cell proliferation. In conclusion, miR-92b-3p inhibited C2C12 cell proliferation by targeting SGK3 and impeded C2C12 cell migration.